IMPLEMENTATION OF THE REGULATION OF THE MINISTER OF MARINE AFFAIRS AND FISHERIES OF THE REPUBLIC OF INDONESIA NUMBER 18 OF 2021 CONCERNING MARINE FISHING EQUIPMENT IN THE CITY OF SIBOLGA FROM THE PERSPECTIVE OF SIYASAH DUSTURIYAH - Muhammad Akhyar Nasution; Khalid Khalid (Program Pascasarjana UIN Sumatera Utara, 2025)
This study analyzes the implementation of the Regulation of the Minister of Marine Affairs and Fisheries of the Republic of Indonesia No. 18 of 2021 concerning Fishing Equipment in Marine Waters in Sibolga City from the perspective of Siyasah Dusturiyah. The research applies a qualitative descriptive method, utilizing field observations, in-depth interviews, and document analysis. Findings indicate that the regulation aligns with sustainable fisheries management principles and has contributed to reducing destructive fishing practices, positively impacting coral reef restoration and fish stock recovery. However, effectiveness remains constrained by limited surveillance capacity, overlapping institutional authority, and the economic burden on small-scale fishers. From the Siyasah Dusturiyah perspective, the policy embodies maslahah ‘ammah but lacks full implementation of al-‘adl, amanah, and syura. Strengthening community participation, providing equitable economic support, and enhancing inter-agency coordination are recommended to balance environmental sustainability with fishermen's welfare.